(untitled) (Journal of Libya for geographical studies, 2021)
The Arctic Oscillation (AO) effects the climate of the northern hemisphere. Several previous studies have been shown the effect of the Arctic Oscillation (AO) on climate conditions in winter in America, Europe, Asia and the Mediterranean region; Therefore, this study attempts to investigate the effect of the Arctic Oscillation (AO) on the mean temperature, As well as the mean maximum and minimum winter temperatures in Libya (December- January-February) by analyzing the correlation for 11 stations over 50 years (1961-2010) and testing it statistically. It was found that the results of the temperature relationship of the winter months are negatively related between the Arctic Oscillation (AO) and all the mean temperatures for the winter months in all the study stations, The study also revealed that the mean January temperature is less correlated with the AO index than the months of December and February. The results also indicate that there is a clear spatial discrepancy with significant statistical significance P-value less than (0.05) between the correlation of the AO index and the mean winter temperature in the west, east and south of the country. Among the results is also that the AO values started to decrease gradually starting from 1991-2010 in all winter months (December-January-February). Which led to the tendency of the mean winter temperature to rise, based on the inverse relationship of the correlation.